Post-coronavirus regional innovation policies: from mega to giga and beyond through sustainable spatial planning of global tourism - Cooke, P.; Nunes, S. (European Planning Studies, 2022)
This contribution is critical of Neo-Schumpeterian innovation studies for a historic tendency to reify ‘industrial’ capitalism as its main conceptual framing model. This includes blind spots concerning the sustainability-free advocacy of ‘green revolution’ chemical fertilizer, pesticide and herbicide practice in industrialist food production. The Coronavirus contagion has alerted regional scientists to these lacunae and this contribution attempts to re-balance the prevailing traditional industrialist bias by considering alternative, more sustainability-informed innovation emphases. These include efforts to conceive innovative sustainable spatial planning models. A particular omission has been re-appraisal of the negative sustainability effects of global tourism. We do this by analyses of ‘territorial innovation’, including considerations of ‘new urbanism’ solutions to prevailing discontents, and advocating ‘GreenSphere’ design of ‘circular economies’ to escape from the negative effects of the environmental despoliation by urban congestion, widespread pollution (including pandemics), global tourism and human well-being. We exemplify the aspects of these conditions by running through three post-urban Model-types–Megacentres (e.g. Bioregional); Gigacentres (e.g. Global Tourism GigaSheds) and GreenSpheres (New Circular Ecologies) before concluding our contribution.